The Lithuanian real estate taxation system in the context of Alien countries - Maliene, Vida; Cibulskiene, Daiva; Gurskiene, Virginija (International Journal of Strategic Property Management, 2010)
The article aims at investigating the Lithuanian real estate taxation system in the context of the taxation system of the United States of America and European countries. The article dwells on the current situation in Lithuania; it introduces the advantages and drawbacks of the system and produces a comparative analysis as against alien countries. Proposals for the refinement of the Lithuanian real estate taxation system are presented on the grounds of the analysis results and alien experience. The article considers real estate tax base, analyses currently actualized tax reforms, and describes the impact of the changes on the real estate market. A number of principal features of real estate tax system commonly intrinsic to all considered countries, such as form of payment, basis of valuation, tax exemption, appeals, tax deductions, are discussed in the article. First Published Online: 18 Oct 2010